Evaluation of Islamic Education: Integrating Cognitive, Moral, and Spiritual Aspects Based on The Qur'an and Hadith - Yuniartin, Titin; Subaidah, Siti; Feriana, Diah; Arman, Muhamad; Saepuloh, Dadang (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to analyze the concept of educational evaluation from an Islamic perspective based on the Qur'an and Hadith, which includes assessing the cognitive, moral, and spiritual aspects of students based on evaluation principles that balance intellectual and spiritual elements in Islamic education. Methodology: This research uses a qualitative method with a literature study approach to understand the phenomenon of educational evaluation in the Qur'an and Hadith. The literature search was conducted through national and international journal articles, critically analyzing the sources to identify key concepts, relevant theories, and significant findings, as well as identifying research gaps. Main Findings: The main findings of this study show that educational evaluation from an Islamic perspective, based on the Qur'an and Hadith, focuses not only on cognitive aspects but also on students' moral and spiritual development. The evaluation process balances intellectual intelligence and piety by assessing character, intention, effort, and devotion. This principle emphasizes the importance of thorough evaluation, both in process and outcome, to form a generation that is knowledgeable, noble, and beneficial to society. Novelty/Originality of this study: The novelty of this research lies in the emphasis on the concept of educational evaluation in Islam that integrates students' cognitive, moral, and spiritual aspects. This research has findings that are different from those of previous research because it emphasizes the balance between intellectual intelligence and character through the principles of the Qur'an and Hadith, which focus on results and a thorough and sustainable evaluation process.